2019
DOI: 10.11159/icgre19.168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Shape of Footing on its Load-Settlement Behaviour (Circular, Square and Rectangular)

Abstract: An experimental investigation is carried out to study the effect of shape of footing on its bearing pressure, when rested on granular soil under centric loading condition. The model footing used in this study are circular, square and rectangle. Rectangular footing used here is a special case of the square footing having L/B ratio of 1.5 and 2 times the width of the square footing. Plate load test is carried out on the dry river sand with two different relative densities (60% and 80%) to obtain the relation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The results revealed that the shape of the footing had a significant effect on the bearing pressure and settlement characteristics. From the above discussion, the results obtained were in line with [40]. It was validated that the square plate performed better in comparison to the circular plate in terms of enhancement in bearing capacity, BCR and SRF.…”
Section: Effect Of Size and Shape On Ultimate Bearing Capacity (Qu) And Settlementsupporting
confidence: 74%
“…The results revealed that the shape of the footing had a significant effect on the bearing pressure and settlement characteristics. From the above discussion, the results obtained were in line with [40]. It was validated that the square plate performed better in comparison to the circular plate in terms of enhancement in bearing capacity, BCR and SRF.…”
Section: Effect Of Size and Shape On Ultimate Bearing Capacity (Qu) And Settlementsupporting
confidence: 74%
“…Vertical stress reaches a constant value which is greater in circular footing by about (70.9 -92.7) % than square footing. The result obtained from the model test performed by Patel and Bhoi [12] on the different footings to examine the influence of footing"s shape on the bearing pressure and settlement showed that the ultimate bearing capacity of the footing increases in order circular, square and rectangle, relative density being 80% . Similar trend is observed for 60% relative density.…”
Section: Effect Of Foundation Shape On the Transmitted Vertical Smentioning
confidence: 99%